Active Aging and Disease Management - Jaime C. Branco (Frontiers Research Topics, 2019)
Population aging and the associated burden of chronic diseases are one of the main challenges in public health worldwide. This Research Topic on "Active Aging and Disease Management" provides a comprehensive overview of population aging through fourteen comprehensive papers. Chapter 1 discusses an overview of health systems in active and healthy aging, while Chapter 2 focuses on the role of lifestyles, exercise and new technologies. Chapter 3 debates psychological and cognitive issues in aging and finally in Chapter 4, an older people self assessment is proposed and the role of communities and supporters are highlighted. We think that real social and health care integration at community level could be the key point to deliver effective health promotion and preventive intervention. Enjoy the reading!